2016
DOI: 10.1007/s00535-016-1224-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of double-coated probiotics for irritable bowel syndrome: a randomized double-blind controlled trial

Abstract: Our result implies that dual-coating layers of probiotic supplement can be a candidate for treatment of diarrhea-predominant irritable bowel syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 42 publications
0
22
0
6
Order By: Relevance
“…The effects of antidepressants, anxiolytics, and even antipsychotics in the treatment of IBS also hint at the correlations between IBS and psychiatric disorders. The recent development of probiotics also found that gut flora could play a role in the development and management of IBS …”
Section: Discussionmentioning
confidence: 99%
“…The effects of antidepressants, anxiolytics, and even antipsychotics in the treatment of IBS also hint at the correlations between IBS and psychiatric disorders. The recent development of probiotics also found that gut flora could play a role in the development and management of IBS …”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated decreased populations of Lactobacillus and Bifidobacterium and an increased presence of Veillonella, Clostridium coccoides, Streptococci , and Coliforms in IBS patients ( Malinen et al, 2005 ; Kassinen et al, 2007 ; Kang and Lee, 2014 ). Thus, therapies aiming to normalize or regulate the unbalanced gut microbiota, such as dietary interventions ( Chey, 2016 ), probiotics ( Han et al, 2016 ) and antibiotics ( Acosta et al, 2016 ), may have therapeutic potential for treatment of IBS.…”
Section: Introductionmentioning
confidence: 99%
“…Kruis et al Os principais sintomas avaliados foram intensidade da dor, desconforto e distensão abdominal, frequência e consistência das fezes. Para essa avaliação, a escala de Bristol foi a mais utilizada (Han et al, 2017;Oh et al, 2019;Lyra et al, 2016;Hod et al, 2018;Yoon et al, 2014).…”
Section: Pré E Probióticos Efeitosunclassified